(untitled) (The Pretoria Student Law Review, 2021)
The aim of this article is to argue that when recognised as persons, women can be independent enough to have the freedom to determine their sexual lives, including what meaning and benefit to derive from their sexual relations.18 Granted that Section 9 of the Constitution enshrines all of our rights to be treated equally as persons, women must be given rights and resources in line with them being equal persons.19 I will further argue that Section 12(2)(b) of the Constitution, to the extent that I relate it to prostitution, imposes a negative obligation on the state to refrain from refereeing sexual conduct.20 This negative obligation applies only to the extent that the sexual conduct in question involves adults who freely consent thereto. Throughout this article, I will argue that women’s vulnerability in prostitution is perpetuated by a continued criminalisation, and the Commission’s recommendation to maintain the status quo does not help to improve the plight of women involved in prostitution. On the contrary, criminalisation victimises prostitutes, and endorses a social stigma associated with prostitution.21 The Commission should have rather devoted its attention to finding solutions on how South Africa can undertake a process of legalising prostitution, and simultaneously address the exploitative nature of prostitution. I will also argue that by virtue of being a politically free society, women involved in prostitution should organise themselves politically, and not rely solely on legal remedies to advance their problems, but rather use political representation as their primary means by which to represent themselves. Have the remedies offered by the South African legal order been exhausted to provide utmost security for sexual freedom?